Non-contiguous finished genome sequence and description of Streptococcus varani sp. nov. (May 2016) - Bakour, S.; Rathored, J.; Lo, C.I.; Mediannikov, O.; Beye, M.; Ehounoud, C.B.; Biagini, P.; Raoult, D.; Fournier, P.-E.; Fenollar, F.
Abstract: Strain FF10 T (= CSUR P1489 = DSM 100884) was isolated from the oral cavity of a lizard ( Varanus niloticus ) in Dakar, Senegal. Here we used a polyphasic study including phenotypic and genomic analyses to describe the strain FF10 T . Results support strain FF10 T being a Gram-positive coccus, facultative anaerobic bacterium, catalase-negative, non-motile and non-spore forming. The sequenced genome counts 2.46 Mb with one chromosome but no plasmid. It exhibits a G+C content of 40.4% and contains 2471 protein-coding and 45 RNA genes. On the basis of these data, we propose the creation of Streptococcus varani sp. nov.